PEMBIASAAN PEMBELAJARAN BERKARAKTER TERHADAP PENGUATAN KARAKTER SISWA SD NEGERI 17 PEKANBARU - Rospika Br. Ginting; Dea Mustika (ADIBA : JOURNAL OF EDUCATION, 2023)
Character education through habituation that has been carried out must be followed by all school members to support the implementation of character education. The forms of habituation that are carried out are divided into 3 namely routine, spontaneous and exemplary habituation. Routine habituation is carried out with several activities such as: praying, flag ceremonies, congregational prayers and reading the Koran/literacy books. Spontaneous habituation is carried out with several activities that emphasize how to speak and act politely. Meanwhile, exemplary habituation emphasizes forms of students' daily behavior such as mutual cooperation, helping each other, being honest, being safe and asking permission when borrowing someone's stuff. The implementation of character learning habituation has been well pursued by schools and most students have implemented it but indeed the implementation has not been optimal due to several obstacles, namely low student awareness of the importance of character habituation, environmental factors that have not supported and become role models for students and uncontrolled use of gadgets.